St. Kitts and Nevis : 2007 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The authorities announced a strategy to restore fiscal and debt sustainability, in conjunction with a transition out of sugar production. Discussions centered on restoring fiscal and debt sustainability, enhancing competitiveness and growth, and containing risks. However, policies need to be strengthened to achieve these targets. Discussions centered on structural reforms to enhance the business climate and improve labor market flexibility, and on releasing government land/assets for more productive uses. Although prudential indicators point to some strengthening of the banking system, its high public sector exposure has increased further.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet